UNITWIN / UNESCO Chairs Programme. Programme UNITWIN / Chaires UNESCO (UNESCO, 2020)
UNITWIN/UNESCO Chairs projects deal with training and research activities and cover all major fields of knowledge within UNESCO's competence such as Education, Natural Sciences, Social and Human Sciences, Culture and Communication and Information. The principal beneficiaries of this programme are institutions of higher learning in developing countries and countries in transition